2022
DOI: 10.3390/ijerph19052601
|View full text |Cite
|
Sign up to set email alerts
|

HIIE Protocols Promote Better Acute Effects on Blood Glucose and Pressure Control in People with Type 2 Diabetes than Continuous Exercise

Abstract: This study compared the acute effects of a session of different high-intensity interval exercise (HIIE) protocols and a session of moderate-intensity continuous exercise (MICE) on blood glucose, blood pressure (BP), and heart rate (HR) in people with Type 2 Diabetes Mellitus (DM2). The trial included 44 participants (age: 55.91 ± 1.25 years; BMI: 28.95 ± 0.67 kg/m2; Hb1Ac: 9.1 ± 2.3%; 76 mmol/mol) randomized into three exercise protocols based on the velocity at which maximum oxygen consumption was obtained (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…As in previous similar experimental and clinical investigations, FBS levels in diabetic rats were significantly reduced following exercise training, although this reduction was more pronounced in the Met-HIIT group [ 23 , 26 , 27 , 28 , 29 ]. However, another study indicated the beneficial effect of MICT in lowering blood sugar in diabetic rats [ 13 ].…”
Section: Discussionsupporting
confidence: 79%
“…As in previous similar experimental and clinical investigations, FBS levels in diabetic rats were significantly reduced following exercise training, although this reduction was more pronounced in the Met-HIIT group [ 23 , 26 , 27 , 28 , 29 ]. However, another study indicated the beneficial effect of MICT in lowering blood sugar in diabetic rats [ 13 ].…”
Section: Discussionsupporting
confidence: 79%
“…In the discussion section, the authors cited the Santiago et al ( 2017) study, which demonstrated reductions in BP and blood glucose after continuous and interval exercise [6]. However, the Santiago study did not cite or analyze glycolytic and oxidative enzymes, as mentioned in the present article: "In addition, there was an increase in the activity of glycolytic and oxidative enzymes" [1].…”
Section: Pointmentioning
confidence: 80%
“…After a careful appraisal, we are concerned that the article "HIIE Protocols Promote Better Acute Effects on Blood Glucose and Pressure Control in People with Type 2 Diabetes than Continuous Exercise" [1] may have some errors that warrant further review by the editor and authors, and which may impact the original article's conclusions.…”
mentioning
confidence: 99%
“…2 Compared with PA performed at lower intensities, high-intensity interval exercise provides cardiovascular health benefits by improving fitness and body composition body mass index and reducing HbA 1c levels in individuals with type 2 diabetes. 2,11 Physical activity metrics such as cadence and the 6-minute walk test (6MWT) reflect PA intensity. 12,13 Cadence is measured in steps per minute.…”
Section: Introductionmentioning
confidence: 99%
“…The American College of Sports Medicine recommends engaging in high-intensity interval exercise regimens involving aerobic training between 65% and 90% VO 2peak or 75% and 95% heart rate peak for 10 seconds to 4 minutes with 12 seconds to 5 minutes of active or passive recovery, in addition to various PA modes, flexibility and balancing exercises, and reducing sedentary time 2 . Compared with PA performed at lower intensities, high-intensity interval exercise provides cardiovascular health benefits by improving fitness and body composition body mass index and reducing HbA 1c levels in individuals with type 2 diabetes 2,11 …”
Section: Introductionmentioning
confidence: 99%